Redox Status, Procoagulant Activity, and Metabolome of Fresh Frozen Plasma in Glucose 6-Phosphate Dehydrogenase Deficiency - Tzounakas, Vassilis L.; Gevi, Federica; Georgatzakou, Hara T.; Zolla, Lello; Papassideri, Issidora S.; Kriebardis, Anastasios G.; Rinalducci, Sara; Antonelou, Marianna H. (Frontiers in Medicine, 2018)
Objective: Transfusion of fresh frozen plasma (FFP) helps in maintaining the coagulation parameters in patients with acquired multiple coagulation factor deficiencies and severe bleeding. However, along with coagulation factors and pro-coagulant extracellular vesicles (EVs), numerous bioactive and probably donor-related factors (metabolites, oxidized components etc.) are also carried to the recipient. The X-linked glucose 6-phosphate dehydrogenase deficiency (G6PD-), the most common human enzyme genetic defect, mainly affects males. By undermining the redox metabolism, the G6PD- cells are susceptible to the deleterious effects of oxidants. Considering the preferential transfusion of FFP from male donors, this study aimed at the assessment of FFP units derived from G6PD- males compared with control, to show whether they are comparable at physiological, metabolic and redox homeostasis levels. Methods: The quality of n=12 G6PD- and control FFP units was tested after 12 months of storage, by using hemolysis, redox and procoagulant activity-targeted biochemical assays, flow cytometry for EVs enumeration and phenotyping, untargeted metabolomics, as well as statistical and bioinformatics tools. Results: Higher procoagulant activity, phosphatidylserine positive EVs, RBC-vesiculation and antioxidant capacity but lower oxidative modifications in lipids and proteins were detected in G6PD- FFP compared with controls. The FFP EVs varied in number, cell origin and lipid/protein composition. Pathway analysis highlighted the riboflavin, purine and glycerolipid /glycerophospholipid metabolisms as the most altered pathways with high impact in G6PD-. Multivariate and univariate analysis of FFP metabolomes showed excess of diacylglycerols, glycerophosphoinositol, aconitate and ornithine but a deficiency in riboflavin, flavin mononucleotide, adenine and arginine, among others, levels in G6PD- FFPs compared with control. Conclusion: Our results point towards a different redox, lipid metabolism and EVs profile in the G6PD- FFP units. Certain FFP-needed patients may be at greatest benefit of receiving FFP intrinsically endowed by both procoagulant and antioxidant activities. However, the clinical outcome of G6PD- FFP transfusion would likely affected by various other factors, including the signaling potential of the differentially expressed metabolites and EVs, the degree of G6PD deficiency, the redox status in the recipient, the amount of FFP units transfused and probably, the storage interval of the FFP, which deserve further investigation by future studies.